Toxicidade da mitomicina C ao endotélio da córnea de coelhos - Bet de Moraes Silva, Maria Rosa [UNESP]; Gregorio, Elisa Aparecida [UNESP] (Conselho Brasileiro de Oftalmologia, 2009)
Purpose: To evaluate corneal endothelium alterations after applying mitomycin C to the sclera using transmission and scanning electron microscopy, correlating alterations with time, concentration, and evaluation methods. Methods: The corneal endothelium of both eyes of 32 albino rabbits was evaluated and distributed into four groups of 8. Mitomycin C was applied under a scleral flap in the right eye for 5 minutes. Mitomycin C concentrations were 0.5 mg/ml for G1 and G2 and 0.2 mg/ml for G3 and G4. Examinations were performed 15 days after application to G1 and G3, and 30 days after application to G2 and G4. Four cornea in each group were prepared for transmission electron microscopy and four for scanning electron microscopy. Left eyes of all animals were used as controls. Results: Transmission electron microscopy showed corneal endothelium alterations in all groups: rarefied cytoplasm, dilation and fragmentation of rough endoplasmic reticulum cisternae, Golgi apparatus with cisternal dilation, reduced vacuoles, and irregularities of internal membrane more noticeable in G1 and G2. Scanning electron microscopy revealed alterations in all groups except G1: changes in the shape and size of cells and longer filopodial projections. Conclusions: 1-Corneal endothelium alterations were seen at both 0.5 and 0.2 mg/ml concentrations and at 15 and 30 days after mytomicin C application; 2 - Alterations were more intense with higher mytomicin C concentration by transmission electron but not by scanning electron microscopy; 3 - The alterations correlated with time by scanning electron microscopy but not by transmission electron microscopy.
Mitomycin C toxicity in rabbit corneal endothelium
Keywords: Endothelium, corneal; Mitomycin/toxicity; Microscopy, electron, transmission; Microscopy, electron, scanning; Aqueous humor/metabolism; Vitreous body; Rabbits